VERPLICHTE PROCUREURSTELLING UNTUK PERADILAN YANG SEDERHANA, CEPAT, DAN BIAYA RINGAN - Suparman, Eman (Veritas et Justitia, 2019)
Civil law suits according to law should be performed in a simple, quick, cost efficient manner.  Notwithstanding that, it is generally known that the procedure of filing and completing a civil law suit is not as easy as it seems. Understandably even the Civil Procedural Law made specifically for the Indonesian population (Het Herziene Indonesich Reglement) made available the ruling that parties may appoint legal counsel to represent them before court.  The author addresses this practice before Indonesian civil court. Data was collected through observation and interviews.  One finding is that almost 90% of all civil court cases registered involves the use of legal counsels.